2019
DOI: 10.3390/vaccines7040187
|View full text |Cite
|
Sign up to set email alerts
|

The Potential of Influenza HA-Specific Immunity in Mitigating Lethality of Postinfluenza Pneumococcal Infections

Abstract: : Influenza virus infections pre-dispose an individual to secondary pneumococcal infections, which represent a serious public health concern. Matching influenza vaccination was demonstrated helpful in preventing postinfluenza bacterial infections and associated illnesses in humans. Yet, the impact of influenza hemagglutinin (HA)-specific immunity alone in this dual-infection scenario remains elusive. In the present study, we assessed the protective effect of neutralizing and non-neutralizing anti-hemagglutinin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 60 publications
0
2
0
1
Order By: Relevance
“…When adding NA to an existing vaccine, addition of extra adjuvants should be avoided, since increased reactogenicity could arise as a consequence. While soluble proteins often are inefficiently immunogenic when unadjuvanted, particle structures often induce immune response without the presence of adjuvanting agents ( 22 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…When adding NA to an existing vaccine, addition of extra adjuvants should be avoided, since increased reactogenicity could arise as a consequence. While soluble proteins often are inefficiently immunogenic when unadjuvanted, particle structures often induce immune response without the presence of adjuvanting agents ( 22 ).…”
Section: Introductionmentioning
confidence: 99%
“…Here, and based on previous work ( 22 24 ), we have generated VLPs in insect cells, that are based on self-assembly and budding of the human immunodeficiency virus 1 (HIV-1) gag protein, and display N2 NA on their surface. N2 was chosen because of the high diversity of H3N2 viruses in the human population and the resulting typically low vaccine effectiveness ( 25 ).…”
Section: Introductionmentioning
confidence: 99%
“…This leads to an increased proliferation of bacteria in the upper and lower respiratory tracts and increases the severity of bacterial complications, such as secondary bacterial pneumonia and otitis media [11]. In a mouse model of parenteral immunization with pseudoviruses containing HA of A/Puerto Rico/8/1934, it was shown that both vaccine-matching and non-matching HA antibodies may reduce morbidity and mortality due to post-influenza pneumococcal infections [12].…”
Section: Introductionmentioning
confidence: 99%
“…Difficulties in developing prophylactic and therapeutic measures against S. aureus emerge from the fact that, organism possesses multiple arsenals of virulence and immune evasion factors, multiple manifestations of infections and our limited understanding of the intricacies of host–pathogen interactions (Fowler and Proctor 2014 ; Reddy et al 2017 ). Lack of protective licensed vaccine combined with dramatic increase of antibiotic-resistant strains in hospital and community at alarming rate has further added to treatment woes (Klausberger et al 2019 ).…”
Section: Introductionmentioning
confidence: 99%